Síntese de 2-trialoacetil-1-metoxicicloalquenos e sua aplicação na obtenção de cicloalcapirazóis e isoxazóis derivados - Costa, Michelle Budke (2008)
This work describes the synthesis and characterization of 2-trihaloacetylmetoxycycloalkenes series derived from cyclical ketones (cyclohexanone, cycloheptanone, cyclooctanone and cyclododecanone). The 2-trihaloacetyl-1-metoxycycloalkenes were obtained from the reaction of trihaloacetylation of 1.1-dimetoxycycloalkanes. Eight 2-trihaloacetyl-1-metoxycycloalkenes have been synthesized, and four of these trichloroacetyl compounds are unprecedented in the literature. The 2-trifluoroacetyl-1-metoxycycloalkenes were employed in the regiospecific synthesis of 3-hydroxy-3-trifluoromethyl-cycloalka[c]isoxazole, 3-trifluoromethyl-cycloalka[c]isoxazole, 3-trifluoromethyl-cycloalka[c]1H-pyrazole, 2-acetyl-3-hydroxy-3-trifluoromethyl-cycloalka[c]1H-pyrazole, 2-carboxyamide-3-hydroxy-3-trifluoromethyl-cycloalka[c]1H-pyrazole, 4-(3-hydroxy-3-trifluoromethyl-cycloalka[c] pyrazole-2-yl]-7-chloroquinoline. The reactions of cyclocondensation employed 2-trifluoroacetyl-1- metoxycycloalkenes and five different 1,2-dinucleofiles (hydroxylamine, hydrazine hydrochloride, acetic hydrazine, semicarbazide and 4-hydrazine-7-chloroquinoline), leading to yield between 34-85%. All compounds were characterized by spectral and analytical experiments, 1H's and 13C's NMR, and its purity was demostrated by CG/MS and elemental analyses.